Cloning and characterization of bgl6111 gene encoding β‐glucosidase from bagasse metagenome - Fitra Adi Prayogo; Benjarat Bunterngsook; Pattanop Kanokratana; Hermin Pancasakti Kusumaningrum; Dyah Wulandari; Anto Budiharjo (Indonesian Journal of Biotechnology, 2023)
β‐Glucosidase (BGL) is an essential enzyme for the hydrolysis of cellulose in industrial processes, but natural BGL enzymes are poorly understood. Metagenomics is a robust tool for bioprospecting in the search for novel enzymes from the entire community’s genomic DNA present in nature. The metagenomics approach simplifies the process of searching for new BGL enzymes by extracting DNA and retrieving its gene information through a series of bioinformatic analyses. In this study, we report the gene cloning, heterologous expression of the bgl6111 gene (accession number MW221260) in Pichia pastoris KM71, and the biochemical characterization of the recombinant enzyme. We successfully identified the bgl6111 sequence of 2,520 bp and 839 amino acids with a molecular size of 89.4 kDa. The amino acid sequence of the bgl6111 gene showed 67.61% similarity to BGL from an uncultured bacterium (ABB51613.1). The BGL product has the highest activity on the third day at 1.210 U/mL, categorized as low production. The enzymatic activity could enhance up to 539.8% of 7.742 U/mL by using the ultrafiltration method. Our findings provide insightful information that bgl6111 obtained from bagasse metagenome could be an alternative candidate for industrial applications in the future.